Languages and the military alliances, occupation and peace building - Footitt, Hilary; Kelly, Michael (Palgrave studies in languages at war, 2012)
For the first time, this book explores the role of foreign languages in military alliances, in occupation and in peace building, through detailed case studies from Ireland, Britain, France, Finland, Slovenia, Korea, Bosnia and Cyprus, ranging from the eighteenth century until today. It adopts a multidisciplinary perspective, bringing together academic researchers and practitioners -- from the military, and from the museum and interpreting worlds. The book raises key issues about communication, identity and representation in war, and argues that the complex linguistic dimensions of conflict and peace operations are of major relevance to military planners, civilian agencies, museums and the media.